Misteria ozyriańskie - widowisko czy rytuał? - Przybyłek, Monika (Collectanea Philologica, 2011)
The article is devoted to the question of ancient Egyptian mysteries of Osiris, god of death and renewable life. During this feast, priests were playing story about the anguish, death, and resurrection of the god. Author attempts to reconstruct course of the performance. Mysteries of Osiris are an unique phenomenon out of one significant reason: they’re ritual as well as performance. Author refers to actual discussion in theatre science about origins of the theatre. It shows that history of theatre can start earlier than in ancient Greece.